Analisis Karateristik Sosial Ekonomi Rumah Tangga Penerima Kartu Keluarga Sejahtera (KKS) di Sumatera Barat - Noari, Sausan Fahira; Marta, Joan (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This research aims to determine the influence of the socio-economic characteristic of household receiving prosperous family cards in West Sumatera Province. In study, there is one variable that has a significant influence namely the percapita expenditure variable which has a probability value 0.000, Partially, there are five variables that are not significant for household receiving prosperous family cards, namely the education variable has probability of 0.933, the age variable has a probability value of 0.154, the employment status variable has a probability of 0.841, and the electric power variable has a probability of 0.440. Based on the reseacrh result, there needs to be extensive and effective socialization by emphasizing that KKS is only for poor household that have been determined by BPS poor household characteristics.